Assessing the Impact of Massive Out-Migration on Albanian Agriculture - McCarthy, Nancy; Carletto, Calogero; Kilic, Talip; Davis, Benjamin (2012)
In this paper, we examine the impacts of migration on household-level farm production decisions, including labor allocation, crop diversification, and agricultural and total household incomes, using household survey data from Albania. Results indicate that increased international migration leads to a reduction in household labor allocated to agricultural activities and crop diversity, but has no impact on agricultural income. However, it does lead to higher total incomes. These findings suggest that international migration does not strengthen household agricultural production but instead facilitates the transition away from agriculture. We also consider the effect on agricultural outcomes of the network of adult children who have left home but are still living in Albania. The effect of this local migration on agriculture is the opposite: larger networks lead to higher agricultural incomes and greater agricultural labor per capita.